Peningkatan Produktivitas Produksi Obat Herbal untuk Peluruh Batu Ginjal di Gapoktan Kelurahan Krapyak Semarang - Ana Hidayati Mukaromah; Nur Hidajah; Triyono Triyono; Sri Suhartati; Yulita Maulani; Vani Intan Krismoni Wiyarti; Thania Ariani Yudimura; Anisa Faradhila; Endang Tri Wahyuni Maharani; Yusrin Yusrin; Herlisa Anggraini (Pelita: Jurnal Pengabdian kepada Masyarakat, 2022)
The Research Program Merdeka Belajar Kampus Merdeka and the Community Dedication based on Research Result is implemented in society. In previous study, Tempuyung and Breadfruit leaves contain flavonoid which can shed kidney stones. The dried Breadfruit leaves contains higher potassium rather than the fresh ones and it’s about 573,68 mg/kg. Ca oxalate was 81.73 % soluble in boiling water of leaf’s breadfruit tea when it consumed once a day for seven days. The method for increasing the production of kidney stone laxative herbal medicines have three steps: preparing the team and partner there are GAPOKTAN Mekar Makmur and Group of society RW VI Krapyak, Semarang. The results of this study need to implemented in society. The step of implementation held in RW VI hall, practice making product of tea bag and brew, also making reports. Based on the questionnaire data, the benefits of this program increase public knowledge about Tempuyung and Breadfruit leaves for shedding kidney stones. The average of increasing knowledge about Breadfruit and Tempuyung leaf goods is 28%, 44% packaging and labelling, and 45% in product marketing. The output is documentation videos, publication in social media, journal community service also the product tea bag and brew of Tempuyung and Breadfruit leaves as well as the other herbal drinks (turmeric, ginger and temulawak).